The Monitoring of Psychosocial Factors During Hospitalization Before and After Cardiac Surgery Until Discharge From Cardiac Rehabilitation: A Research Protocol - Callus, Edward; Pagliuca, Silvana; Bertoldo, Enrico Giuseppe; Fiolo, Valentina; Jackson, Alun Conrad; Boveri, Sara; De Vincentiis, Carlo; Castelvecchio, Serenella; Volpe, Marianna; Menicanti, Lorenzo (Frontiers in Psychology, 2020)
Introduction: there is considerable evidence that psychosocial factors contribute in the etiology and the prognosis of cardiac illness. Currently, in Italy, psychologists are only obligatory in the cardiac rehabilitation setting, although there are indications that the patients could be experiencing distress also during other moments of hospitalization, when admitted for cardiac surgery. Objective and methods: the objective of this protocol is to gain more information about the cardiac patients, specifically during the various moments of hospitalization for cardiac surgery, by collecting data at admittance before cardiac surgery (t0), at admittance in cardiac rehabilitation (t1) and at discharge (t2) at the IRCCS Policlinico San Donato Hospital. A psychosocial questionnaire was constructed after consulting the relevant national and international guidelines. Patients admitted for cardiac surgery and attending a rehabilitation program, will be evaluated by acquiring data about their civil status, religiosity, education and work capacity, social condition (including the presence and quality of intimate relationships and support received), previous psychological and psychiatric history, psychological status, lifestyle (including questions on nutrition, smoking, alcohol and substance abuse, with the administration of the Fagerström test for smokers), adherence to therapy (Morinsky test) quality of life (Satisfaction with Life Scale and a numerical rating scale ranging from 0-100), health perception (EuroQoL,only the numerical rating scale 0-100) and anxiety and depression (Hospital Anxiety and Depression Scale) at t0. Health perception, anxiety and depression are also measured at t1 and t2. Discussion and conclusions: This study is an attempt to identify the recommended psychosocial variables whichwhich need to be monitored during the cardiac patients’ hospitalization for cardiac surgery, until cardiac rehabilitation. After implementing this study at the IRCCS Policlinico San Donato, attempts will be made to create studies on a national and international level to generate more evidence regarding these variables, in order to create tailor made interventions for these patients during these specific and delicate moments.